Budgeting for managers - Kemp, Sid; Dunbar, Eric (McGraw-Hill's AccessEngineering., 2003)
"Starts with the basics of a simple expense budget and gives you everything you need to know to create, present and track a budget with a spreadsheet or accounting package. From definitions of fundamental accounting terms to techniques for working within your budget and managing money with your team, it will take you through the basics and beyond"--Back cover.